Sampling plan of SB Brasil 2023: precision of dmft and DMFT estimates for the study domains - Maria Cecília Goi Porto ALVES; Gizelton Pereira ALENCAR; Andrea Maria Duarte VARGAS; Raquel Conceição FERREIRA; Regina Tomie Ivata BERNAL (Brazilian Oral Research)
Abstract The oral health surveys conducted in Brazil since the 1980s, aligned with the guidelines of the National Oral Health Policy, have been essential for epidemiological surveillance. Over the surveys, variations in the applied sampling plans have occurred, including changes in the study domains. In SB Brasil 2023, an effort was made to meet the demands of state managers by expanding the domains including Federative Units and capitals. This study presents the sampling plan and assesses the precision of dmft and DMFT estimates for the defined domains. The sampling process was stratified (capitals and interior of the Federative Units) and involved a two-stage cluster design (census tract and households) for the age groups 15–19, 35–44, and 65–74 years, while a single-stage design was used for the ages of 5 and 12 years. The planned sample size was 250 (for ages 5 and 12) or 300 (for the other age groups) in the capitals, with an additional 100 interviews in the interior to obtain estimates for the Federative Units. The number of census tracts in each stratum was determined to achieve 250 interviews for the ages of 5 or 12 years. During the data analysis phase, base weights were adjusted through post-stratification based on sex, age, and education level, using data from the 2022 Continuous National Household Sample Survey, aiming to minimize selection and response biases. The dmft and DMFT estimates were evaluated using the coefficient of variation. Most estimates were precise, both for the capitals and for the Federative Units, with greater precision in the capitals.